Development of a Lived Experience-Based Digital Resource for a Digitally-Assisted Peer Support Program for Young People Experiencing Psychosis - Peck, Claire E.; Lim, Michelle H.; Purkiss, Melanie; Foley, Fiona; Hopkins, Liza; Thomas, Neil (Frontiers in Psychiatry, 2020)
This paper describes the creation of a web-based digital resource designed for tablet computer use during peer work sessions to structure discussion about recovery in early psychosis. The resource consisted of a series of videos featuring young people discussing how they navigated issues in their own recovery. A participatory process was used to create the resource. Researchers held a series of collaborative development workshops with young people, peer workers, other mental health practitioners and academics. These were used to derive a framework of recovery processes relevant to young people experiencing psychosis, which was considered as useful areas of discussion within a peer work relationship. A semi-structured interview guide based on this framework was then used in video-recorded interviews with young people in recovery from psychosis. Footage was edited into 14 videos and organised into six final themes: My Journey, Self-Care, Connections, My Identity, Life and Mental Health. The combined expertise of young mental health service users, peer support workers, mental health practitioners and digital mental health researchers throughout the development process enabled the creation of tailored digital resource for peer work in early psychosis. The final content themes bore similarities to models of personal recovery developed in adult services with some key differences for a younger population.